Pengaruh Kemampuan Komunikasi dan Pemecahan Masalah Matematika terhadap Hasil Belajar Siswa dengan Pembelajaran Realistic Mathematic Education (RME) - Kusumawati, Noviana (Delta Jurnal Ilmiah Pendidikan Matematika FKIP Universitas Pekalongan, 2013)
The objectives of this research are to investigate: whether the communication and problem solving skills have a positive influence on student learning outcomes, especially in solving math problems and if there is how much of influence. The variables of this research are communication skills (X1), problem solving skills (X2) and student learning outcomes (Y). The research process was conducted in 3 stages, first to investigate the influence of communication and problem solving skills againts on student learning outcomes, both to investigate the influence of communication skills on learning outcomes and three to investigate the influence of problem-solving skills of students’ learning outcomes. The results of this research are as follows: from the calculation of data obtained regression equations are , dual correlation coefficients X1 and X2 of Y is 0,567 with a coefficient of determination 0,322. Parsil correlation coefficient between Y and X1 with regard X2 to the rates fixed are 0,324 with a coefficient of determination 0,104 and parsil correlation coefficient between Y and X1 with regard X2 to the rates fixed are 0,166 with a coefficient of determination 0,028. Conclusions is that there are influence of communication and problem solving skills simultaneously against student learning outcomes is equal to 32.2%, while the influence of the communication skills of student learning outcomes are 10,4% and the influence of problem-solving skiils of the student learning outcomes at 2,8%. Therefore, in learning mathematics material fractions, teachers are advised to use RME learning to improve students’ activeness in solving math problems so can improve communication and problem-solving skills, which in turn can improve student learning outcomes. Key words: Communication and Problem Solving Skills, RME Learning, Learning Outcomes, Fraction.